ANALISIS BAHASA SINGKATAN DAN EMOTIKON PADA APLIKASI INSTAGRAM SEBAGAI CIRI KOMUNIKASI DIGITAL MAHASISWA UNPARI - Dwi Anggita; Yulia Nirmalasari; Tita Kurnia Sari; Tiara Agma (LPPM Universitas PGRI Silampari Lubuklinggau, 2026)
This study aims to describe the form, function, and meaning of the use of abbreviations and emoticons on Instagram as a characteristic of digital communication among the UNPARI students. The method used is descriptive qualitative. The research procedure includes data collection, data classification, data analysis, and conclusion drawing. The research data consists of written utterances containing abbreviations and emoticons, while the data sources come from posts, comments, and messages on the Instagram application used by the UNPARI students. Data collection techniques were conducted through documentation and recording. Data analysis was conducted by identifying the forms of abbreviations and emoticons, grouping them based on type and function, and then interpreting their meaning in the context of digital communication. The results show that abbreviations and emoticons are used to streamline message delivery, express emotions, reinforce the intent of speech, and foster familiarity among Instagram users. The use of these elements also reflects linguistic creativity and the community's adaptation to developments in social media. Furthermore, the use of abbreviations and emoticons is influenced by factors such as the communication situation, social relationships between users, and the local cultural context. The conclusion of this study is that abbreviated language and emoticons on Instagram are important characteristics of digital communication in the UNPARI students community, serving as a means of conveying messages and expressing identity and social relations in the digital space.